2023
DOI: 10.7759/cureus.43215
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Assessment in Endodontics Among Undergraduate Students

Abstract: To explore perceptions of undergraduate dental students regarding difficulties faced during endodontic procedures. MethodsAn e-questionnaire was sent to 57 fourth-year and 45 fifth-year dental students. It comprised questions regarding demographic data and difficulties faced during different steps of the endodontic treatment. The responses were recorded on a 5-point Likert scale. During dichotomization, responses where one and two were chosen were considered yes whereas responses where three, four, and five we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The difference between this study's results and Alrahabi [ 3 ] is that the cases that are referred to the dental students in both KSU and KSAUHS are screened in advance. In 2023, Almutairi et al [ 10 ] concluded that the academic level did not significantly affect the student confidence while performing root canal treatment except in taking x-rays in mesial or distal shift.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between this study's results and Alrahabi [ 3 ] is that the cases that are referred to the dental students in both KSU and KSAUHS are screened in advance. In 2023, Almutairi et al [ 10 ] concluded that the academic level did not significantly affect the student confidence while performing root canal treatment except in taking x-rays in mesial or distal shift.…”
Section: Discussionmentioning
confidence: 99%